Sociocultural barriers to emotional regulation in Andean adolescents, a qualitative-quantitative approach - Aldazábal Contreras, Ana (2023)
The purpose of this research was to record the sociocultural barriers to emotional regulation in Andean adolescents applying to a higher pedagogical institute in Ancash. The sequential transformative mixed design research model was developed in the Andean zone of the Ancash region (Peru). The study unit was male adolescents (N = 24), between 16 and 18 years of age, applicants to a private pedagogical institute, who interact in a homosocial boarding school context. This emotion regulation program was designed consisted of 12 sessions of 90 minutes each. The quantitative data collection instrument (pre and post test) was the Emotional Regulation Difficulties Scale (DERS) by Gratz and Roemer (2004), adapted by Huamaní y Saravia (2017) for the Arequipa region population, validated by judges' criteria for the Andean population of the Ancash region. For the qualitative data, two individual semi-structured interviews were applied, and records the observation of the dynamics among participants in each of the sessions in this program. An improvement in emotional awareness was evidenced. There were no changes in emotional rejection, strategies and goals, due to sociocultural barriers resulting from a socialization based on the traditional masculinity model existing in the Andean region Fuller (2001). Based on the results, it is recommended that emotional education programs for men should consider sociocultural and gender variables.